Efficacy and safety of recanalization therapy for acute ischemic stroke with COVID-19: A systematic review and meta-analysis - Wang, Zilan; Teng, Haiying; Wu, Xiaoxiao; Yang, Xingyu; Qiu, Youjia; Chen, Huiru; Chen, Zhouqing; Wang, Zhong; Chen, Gang (Frontiers in Neurology, 2022)
BACKGROUND: The novel coronavirus disease 2019 (COVID-19) has rapidly spread worldwide and created a tremendous threat to global health. Growing evidence suggests that patients with COVID-19 have more severe acute ischemic stroke (AIS). However, the overall efficacy and safety of recanalization therapy for AIS patients infected by the SARS-CoV-2 virus is unknown. METHODS: The PRISMA guideline 2020 was followed. Two independent investigators systematically searched databases and ClinicalTrials.gov to identify relevant studies published up to March 31, 2022. AIS patients who received any recanalization treatments were categorized into those with COVID-19 and those without COVID-19. The main efficacy outcomes were patients' functional independence on discharge and successful recanalization, and the safety outcomes were in-hospital mortality and symptomatic intracranial hemorrhage. Subgroup analyses were implemented to assess the influence of admission National Institutes of Health Stroke Scale and different recanalization treatments on the outcomes. STATA software 12.0 was used for the statistical analysis. RESULTS: This systematic review and meta-analysis identified 10 studies with 7042 patients, including 596 COVID-19 positive patients and 6446 COVID-19 negative patients. Of the total patients, 2414 received intravenous thrombolysis while 4628 underwent endovascular thrombectomy. COVID-19 positive patients had significantly lower rates of functional independence at discharge (odds ratio [OR] 0.30, 95% confidence interval [CI] 0.15 to 0.59, P = 0.001), lower rates of successful recanalization (OR 0.40, 95% CI 0.24 to 0.68, P = 0.001), longer length of hospital stay (weighted mean difference 5.09, 95% CI 1.25 to 8.94, P = 0.009) and higher mortality rates (OR 3.38, 95% CI 2.43 to 4.70, P < 0.0001). Patients with COVID-19 had a higher risk of symptomatic intracranial hemorrhage than the control group, although the difference did not reach statistical significance (OR 2.34, 95% CI 0.99 to 5.54, P = 0.053). CONCLUSIONS: Compared with COVID-19 negative AIS patients who received recanalization treatments, COVID-19 positive patients turned out to have poorer outcomes. Particular attention needs to be paid to the treatments for these COVID-19 patients to decrease mortality and morbidity. Long-term follow-up is necessary to evaluate the recanalization treatments for AIS patients with COVID-19.